Representation of Climate Change in the Documentary Film Ano Bulan Balong (Semiotic Analysis of Roland Barthes) - Sufriatni, Sufriatni; SF, Aka Kurnia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Climate change is a condition characterized by changes in world climate patterns which result in erratic weather phenomena. Climate change occurs due to changes in climate variables, such as air temperature and rainfall, which occur continuously. In this research, film is the subject, film is a mass communication tool that is packaged with characters, plot and messages in it, provides information to the audience through the storyline that is conveyed and has a strong influence on issues that are developing in society, the unit of analysis of this research contains